Biofertilizer gives boost to yields - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1998)
More than two thousand smallholder farmers on communal land in Mashonaland, Zimbabwe are now obtaining soybean yields which are comparable to those on large commercial farms. Since 1996, Mashonaland farmers, who traditionally cultivated maize, have...